EXPERIENTIAL TRAINING FOR MULTILINGUAL COMMUNITIES - Donald Sargeant (Universitas Negeri Padang, 2016)
The rationale behind this paper is that teachers will teach in ways that they have been taught and trained as teachers. Most training programmes prepare teachers to teach communicatively, but unfortunately few pay any attention to the fact that most teachers will probably be teaching English in Multilingual communities. It is my belief that lecturing teachers on communicative methodology will not be successful in helping them to teach communicatively in the classroom or prepare them to work in multilingual environments. In our training in Omani Training Centres, we adopt an experiential approach and this paper seeks to justify this by showing how it is collaborative and will lead to teacher autonomy and ultimately we hope to the encouragement of independent learning in the schools. In this approach our participants will experience different techniques and afterwards they will reflect on such educational issues as classroom management, learning styles, learner independence and collaborative learning. We also do not neglect the role of translation, but ensure that this is done in a communicative way. This paper will show how this can be done by examining several of the techniques that I use in training.